Deindividuation Phenomenon among Anonymous Kpopers Account on Social Media X - Raisyah Siti Hafifah; Nurrahmi, Febri (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Social media X allows its users to use anonymous accounts and hide their identities, leading Kpopers to prefer interacting anonymously. This study aims to describe the phenomenon of deindividuation that occurs among Kpopers using anonymous accounts on social media X. This study uses Social Identity of Deindividuation Effect (SIDE) theory. Deindividuation refers to a state where the individual acts differently than usual because considers theirself to be part of group. It employs a descriptive qualitative method with a phenomenological approach and data collection techniques through semi-structured interviews with five anonymous Kpopers account users who actively interact on social media X. Observation and documentation of comments and activities of the informants on social media X were also conducted. The research results show that deindividuation can be seen in the anonymous Kpopers accounts on social media X when they use a fan account. The use of anonymous accounts causes user behavior to prioritize their identity as Kpopers and place greater importance on group norms rather than their personal norms. This deindividuation phenomenon occurs due to three factors, including anonymity, group immersion, and reduced identifiability. The anonymity factor occurs because anonymous Kpopers account users feel more comfortable and freer to express their opinions as Kpopers due to negative stigma towards those who idolize Kpop when revealing their real identity. Individuals first became Kpopers and did not experience group immersion, but when they joined social media X using an anonymous account, they began to show symptoms of group immersion. By joining the Kpopers group and using anonymous accounts as their identity, they focus more on their identity as Kpopers rather than as individuals. This causes them to start forgetting their personal identity (reduced identifiability).